2023
DOI: 10.1111/ans.18195
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of volatile organic compound breath testing in the Australasian colorectal cancer pathway

Abstract: With colonoscopy resources under pressure and inequitable participation rates in our screening programmes, there is an urgent need to consider trialling new testing technology for the detection of colorectal cancer (CRC) in Australasia. Research has shown that volatile organic compounds (VOCs) emitted from the human body can act as biomarkers for CRC, indicating high sensitivity and specificity for early and late-stage CRC and for adenomatous polyps. Breath-based VOC testing shows promise due to acceptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Meanwhile, FIT tests are not ideal, due to their low sensitivity to detect early-stage, small-size, and proximally located neoplasms [32]. Hence, the sensor technology is currently of utmost interest [27,33].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, FIT tests are not ideal, due to their low sensitivity to detect early-stage, small-size, and proximally located neoplasms [32]. Hence, the sensor technology is currently of utmost interest [27,33].…”
Section: Discussionmentioning
confidence: 99%
“…Different chemical compounds including hexanal, propanal, pentanal, acetone, pentane, 2butanone, and benzene at specific concentrations have been identified as potential lung cancer biomarkers 104 . Overall, there is growing evidence that VOCs in the breath of cancer patients are altered compared to healthy individuals [105][106][107][108] , and these unique compositions of VOCs in exhaled human breath can be used as a fingerprint for the early detection of cancer. We have shown that honeybees can detect all nine of the different lung cancer associated VOCs we tested, indicating their capacity to be a breath-based diagnostic sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, their production and release may be altered in some diseases, such as cancer [5,11]. Therefore, VOMs represent a patient's metabolic fingerprint, comprising endogenous and exogenous factors, and for these reasons, have been proposed as a promising class of disease biomarkers (Figure 1) [8,12]. VOMs have been highlighted in recent studies because of their ease of use and noninvasiveness, as they can be identified in easily accessible biofluids such as urine, saliva, and exhaled breath [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Volatilomic analysis involves sensitive analytical techniques such as mass spectrometry (MS), electronic nose (e-nose), or sensor techniques combined with multivariate statistical analysis to characterise the chemical composition of biological fluids [11,15]. MS techniques identify and quantify the levels of VOMs, whereas e-nose sensor arrays are linked to pattern recognition algorithms or chemical sensor systems [10,12]. Legend: Acc: accuracy; ANN: artificial neural networks; AUC: area under the receiver operating characteristic (ROC) curve; CART: classification and regression tree; CER: classification error rate; CNN: convolutional neural network; CV: cross-validation; GC-IMS: gas chromatography-ion migration spectroscopy; GC-MS: gas chromatography-mass spectrometry; GC-TOF-MS: gas chromatography coupled to time-of-flight mass spectrometry; HPPI-TOFMS: high-pressure photon ionization time-of-flight mass spectrometry; HS: headspace; HS-SPME: headspace solid-phase microextraction; MLR: multiple logistic regression; NA: not analyzed; PCa: prostate cancer; PCA: principal component analysis; PLS-DA: partial least-squares discriminant analysis; PTR-TOF-MS: proton-transfer-reaction time-of-flight mass spectrometry; RF: random forest; ROC: receiver operating characteristic; Sens: sensitivity; SIFT-MS: selected ion flow tube-mass spectrometry; Spec: specificity; SVM: support vector machine; TD-GC-MS: thermal desorption gas chromatography-mass spectrometry; TD-GC-TOF-MS: two-dimensional gas chromatography with time-of-flight mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation